Nanocarrier-based hydrogel of betamethasone dipropionate and salicylic acid for treatment of psoriasis - Baboota, Sanjula; Alam, Md Sarfaraz; Sharma, Shrestha; Sahni, Jasjeet K; Kumar, Anil; Ali, Javed (International Journal of Pharmaceutical Investigation)
Introduction: Betamethasone dipropionate (BD) has anti-inflammatory, immunomodulatory, and antiproliferative activity. The aim of the current work was to test the hypothesis that the addition of corticosteroid such as BD and a keratolytic agent such as salicylic acid in nanocarrier based microemulsions formulation would result in enhancement and sustaining of corticosteroid delivery rate leading to better anti-psoriatic activity. Clinical use of BD is restricted to some extent due to its poor permeability across the skin. So to increase its permeation across the skin, microemulsion-based gel formulations were prepared and characterised. Materials and Methods: Microemulsions were prepared by aqueous phase titration method, using oleic acid:sefsol (1.5:1), Tween 20, isopropyl alcohol, and distilled water as the oil phase, surfactant, cosurfactant and aqueous phase, respectively. Selected formulations were subjected to physical stability studies and consequently in vitro skin permeation studies. Surface studies of optimized formulation were done by transmission electron microscopy. In vivo anti-inflammatory activity was done by carageenan-induced raw paw edema method. Results: The droplet size of microemulsions ranged from 60 to 190 nm. The optimized formulation exhibited viscosity 28.55 ± 2.03 mP, refractive index 1.409, pH 6.4, and conductivity 10-4 scm-1. The optimized microemulsion was converted into hydrogel using carbopol 934, and salicylic acid was incorporated into it. Drug deposition in skin was found to be 29.73 μg/mg. Assessment of skin permeation was done by histopathology studies which indicated changes in the structure of epidermal membrane of skin. In vivo anti-inflammatory activity indicated 72.11% and 43.96% inhibition of inflammation in case of developed microemulsion gel and marketed gel, respectively. Conclusions: The developed microemulsion gel containing BD and salicylic acid provided sustained and good anti-inflammatory activity for the treatment of psoriasis.
Keywords: Betamethasone dipropionate; microemulsions; salicylic acid; transmission electron microscopy